PERBEDAAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMP ANTARA SISWA YANG DIAJAR DENGAN PENDEKATAN MATEMATIKA REALISTIK DAN PEMBELAJARAN KONVENSIONAL - Maxtulus Junedy Nababan (Universitas Quality, 2019)
This study aims to determine the differences in mathematical communication skills of students taught with realistic mathematical approaches and conventional learning. The results of this study are mathematical communication skills of students who are taught with realistic mathematical approaches higher than the mathematical communication skills of students who are given conventional learning. A realistic mathematical approach is able to become students to achieve the minimum completeness criteria for classical student learning outcomes. While conventional learning is not able to become students to achieve the minimum completeness criteria for classical student learning outcomes